Penyelesaian Vehicle Routing Problem with Simultaneous Pick Up and Delivery dengan Algoritma Tabu Search - Garside, Annisa Kesy; Cahyanti, Dian Nur (Program Studi Teknik Industri, Universitas Muhammadiyah Surakarta, 2018)
Vehicle routing problem with simultaneous pickup and delivery (VRPSPD) is a problem of vehicle routes where the delivery and pickup of products to each consumer is conducted simultaneously. Pangkalan Agisindo Alam Mandiri is engaged in the distribution of 3 kg LPG. At present,pangkalan already has a schedule of visits to retail stores, but the visit route is still subjectively set which causes long mileage and high transportation costs. The problem of determining the route at this pangkalanis calledVRPSPD because pangkalandelivered filled LPG tubes to retail stores and at the same time picked up empty LPG tubes to be brought back. To determine the route, one must consider the vehicle capacity and the ratio of the number of LPG tubes delivered and picked up. This research used a tabu search algorithm to get the proposed route. The steps in the tabu search algorithm includes determination of the initial solution, the neighborhood search, intensification phase, diversification phase, standard phase, and interactive phase. By using the tabu search algorithm, the proposed route provided a savings of transportation costs of 13.72% rather than the initial route of the company.